2020
DOI: 10.1101/2020.06.05.20123471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of disease duration and symptom course of outpatients with acute covid-19: a retrospective cohort study

Abstract: Objective: To describe the symptom course in outpatients with coronavirus disease 2019 (COVID-19). Design: Retrospective chart review of standardized symptom checklist for patients followed at home by telephone calls during their acute COVID-19 illness. Compile results by day of illness into a single heatmap representation of symptoms. Setting: COVID-19 Virtual Outpatient Management Clinic (VOMC) in Atlanta, Georgia; a practice that follows patients with mild COVID-19 at home. Participants: 272 patients with c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
(21 reference statements)
2
13
0
Order By: Relevance
“…In contrast to hospitalized COVID-19 patients, conventional risk factors such as age and the presence of comorbidities do not seem to have an impact on the duration and severity of persistent symptoms. A study by O’Keefe et al (2020) analyzed 273 non-hospitalized patients recovering from COVID-19. Interestingly, the authors found no correlation between symptom duration and patient factors such as age or comorbidities.…”
Section: Persisting Cariorespiratory Symptoms In Coronavirus Survivormentioning
confidence: 99%
“…In contrast to hospitalized COVID-19 patients, conventional risk factors such as age and the presence of comorbidities do not seem to have an impact on the duration and severity of persistent symptoms. A study by O’Keefe et al (2020) analyzed 273 non-hospitalized patients recovering from COVID-19. Interestingly, the authors found no correlation between symptom duration and patient factors such as age or comorbidities.…”
Section: Persisting Cariorespiratory Symptoms In Coronavirus Survivormentioning
confidence: 99%
“…Previous studies reported that the most common initial symptoms are systemic, upper respiratory and cough. Lower respiratory and gastrointestinal symptoms are less frequent and generally appear at the late stage of the disease [ 3 ]. The symptoms, if present, of longest duration are cough, loss of sense of smell or taste, sinus congestion, shortness of breath upon exertion, body aches, and headache [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lower respiratory and gastrointestinal symptoms are less frequent and generally appear at the late stage of the disease [ 3 ]. The symptoms, if present, of longest duration are cough, loss of sense of smell or taste, sinus congestion, shortness of breath upon exertion, body aches, and headache [ 3 ]. A study about the time that COVID-19 patients required to achieve a usual state of health reported that sixty-five percent have returned to their usual state of health 7 days from the date of diagnosed, whereas 35% of patients had not returned to their usual state of health, 12–14 days after receiving a positive test result [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two prepeer-reviewed studies with longitudinal follow-up for non-hospitalized patients revealed that, on average, symptoms in outpatients resolved after 3 weeks with a standard deviation of 1.25 weeks, not accounting for the possibility that an employee's symptoms could worsen, requiring hospitalization and extending his or her absence. 2,3 We have found no data nor proxy for estimating the recovery time after discharge, though we would expect that those hospitalized, especially those requiring intensive care, would need extensive time to recuperate prior to re-entering the workforce.…”
Section: Disease Course Of Covid-19mentioning
confidence: 99%